Asmeninių kompetencijų reikšmė tarpdisciplininės komandos veikloje - Gevorgianienė, Violeta (Socialinė teorija, empirija, politika ir praktika, 2014)
Vilniaus universitetasSocialinio darbo katedraUniversiteto g. 9/1 – 309 kab.LT-01513 VilniusTel. 8 615 17 924El. paštas: violeta.gevorgianiene@fsf.vu.ltŠio straipsnio tikslas – remiantis skirtingoms disciplinoms atstovaujančių specialistų nuomonių tyrimu aptarti asmeninių kompetencijų reikšmę tarpdisciplininių ankstyvosios intervencijos vaikystėje komandų veiklai. Įvairioms profesinėms sritims atstovaujančių specialistų kompleksinė pagalba rizikos situacijoje esančiam žmogui reikalauja darnių veiksmų. Tokių veiksmų sėkmė priklauso ne tik nuo sprendžiamos problemos sudėtingumo, bet ir nuo kompetencijų, kurias demonstruoja atskiri komandos nariai ir visa komanda. Ankstyvosios intervencijos tarnybų specialistų sudaryti kompetencijų sąrašai parodė, kad dabartiniame tarpdisciplininio bendradarbiavimo etape (nesant senų tokio bendradarbiavimo tradicijų) didžiausia reikšmė yra skiriama komandos nario geranoriškumui ir atvirumui patirčiai.Pagrindiniai žodžiai: tarpdisciplininė komanda, asmeninė kompetencija, refleksija.THE SIGNIFICANCE OF PERSONAL COMPETENCIES IN THE WORK OF AN INTERDISCIPLINARY TEAMVioleta GevorgianienėSummaryA complex support of a person in a difficult life situation requires coordinated efforts of specialists representing various professional fields. The quality of support and successful interdisciplinary team work in general depends not only on the complexity of the task, but also on competencies demonstrated by individual members of a team and the whole team in general. In the article the significance of personal competencies in interdisciplinary teams is analysed, based on the opinions survey of professionals working in early childhood intervention services. The method of expert evaluation (questionnaire) was used. Respondents were asked to compose two lists of competencies: firstly, to cognitively reflect on competencies which they considered important for the team work and, secondly, to recall most important competencies which they observed in practice and which most contributed to the successful team work. The lists of competencies composed by professionals revealed that in the current stage of interdisciplinary cooperation (when traditions of common work of different professionals are not yet strong) experts allocate the highest importance to competencies closely related to personal qualities of a colleague, such as agreeableness (revealed in the cognitive reflection) and openness to new experience (revealed in practice reflection).Key words: interdisciplinary team, personal competence, reflection.